TECOS Finds Sitagliptin Does Not Increase Heart Failure Risk. Issue 28 (29th October 2015) - Cunningham, Muriel
TECOS was a large randomized placebo-controlled trial in patients with type 2 diabetes mellitus and cardiovascular disease, conducted to demonstrate the noninferiority of sitagliptin as compared with placebo in the risk of cardiovascular events. A prespecified secondary analysis found no impact of sitagliptin on heart failure hospitalization or related events.